Electrical conductivity measurements in evaporated tin sulphide thin films - Deraman, Karim (Taylor & Francis, 1994)
Tin sulphide (SnS) has been evaporated on to substrates maintained at fixed temperature in the range 50-300 oC. X-ray diffraction measurements have shown that the films deposited at the lower substrate temperatures are non-stoichiometric, containing higher sulphides of tin, but that those deposited at 300 oC consist essentially only of SnS. Film conductivity increased in the range 0.5-2.0 S m-1 as the substrate temperature during deposition increased from 50 oC to 250 oC, this effect being attributed to the changing film composition. Films deposited at 50 oC and 150 oC showed thermally activated conductivity at temperatures above 220-250K, with activation energies Ea of 0.12 eV and 0.14 eV, respectively. At lower temperatures both conductivity and activation energy were considerably lower, consistent with hoping via localized states. The conductivity is modified after prolonged cooling to 160 K, although the mechanism of this process is not understood.